Taxonomy and lectotypification of Lepidagathis hamiltoniana (Acanthaceae: Barlerieae), an endemic species of India - King, A.F.J.; Prajapati , S.R.; Patel , R.M.; Gnanasekaran , G.; Darbyshire , I.; Arisdason, W. (Rheedea, 2023)
The taxonomy of Lepidagathis hamiltoniana Wall. ex Nees (Acanthaceae: Barlerieae) is discussed, along with a detailed description, illustration and photo plates. The taxonomic complexities among L. collina (Endl.) Milne-Redh., L. cristata Willd. and L. hamiltoniana are clarified. Lectotypes for the names, L. beddomei T.Anderson and L. hamiltoniana are designated here.